The Impacts of PETI on the Batang Hari River to the Decline of Water Quality, Land Transfer Function, Socio-Cultural Life and the Community Economy - Desrizal, Desrizal; Carlo, Nasfryzal; Syah, Nurhasan (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
One of the Batang Hari watersheds flows in the Jorong Gasing area of Nagari Lubuk Ulang-Aling, Sangir Batang Hari. In this area, for generations, people use river water for various activities such as irrigating rice fields, transportation facilities, inland fisheries, and toilet washing facilities. But a few years ago there began to be an Unlicensed Gold Mining (PETI) activity. As a result, the condition of the Batang Hari river is alarming, as the level of turbidity is very high, damage to the right-left border of the river, destruction of forest areas, and even affect the social and economic life of the community. Therefore, this research was conducted to describe and prove the full impact of the PETI activity. The results showed a decrease in the quality of Batang Hari Hari river, specifically TSS parameters. The over function land was very significant where land cover in 2000 was 61.22 ha of secondary dryland forest to 25.18 ha in 2017. There was evidence of changes in socio-economic life with 63% of the surrounding community no longer utilizing river water, mutual cooperation activities are decreasing, conflicts often occur, as well as an increase in the economy but its growth is unpredictable.